2016
DOI: 10.1007/s00253-016-7697-z
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic activation of a thermostable glutamyl endopeptidase capable of hydrolyzing proteins at high temperatures

Abstract: Glutamyl endopeptidases (GSEs) specifically hydrolyze peptide bonds formed by α-carboxyl groups of Glu and Asp residues. We cloned the gene for a thermophilic GSE (designated TS-GSE) from Thermoactinomyces sp. CDF. A proform of TS-GSE that contained a 61-amino acid N-terminal propeptide and a 218-amino acid mature domain was produced in Escherichia coli. We found that the proform possessed two processing sites and was capable of autocatalytic activation via multiple pathways. The N-terminal propeptide could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Meanwhile, the highly abundant no-rank Actinobacteria in JF liquor starter (J3 and J4) could produce volatile organic compounds; the secondary metabolic products of Actinomyces could also contribute to flavor development 38 . Thermoactinomyces can produce plenty of thermostable extracellular proteolytic enzymes, e.g., alkaline proteinase 39 , glutamyl endopeptidase 40 and carboxypeptidase 41 . This study further found that Bacillales and no-rank Actinobacteria were the dominant communities when the temperature increased to the highest point.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the highly abundant no-rank Actinobacteria in JF liquor starter (J3 and J4) could produce volatile organic compounds; the secondary metabolic products of Actinomyces could also contribute to flavor development 38 . Thermoactinomyces can produce plenty of thermostable extracellular proteolytic enzymes, e.g., alkaline proteinase 39 , glutamyl endopeptidase 40 and carboxypeptidase 41 . This study further found that Bacillales and no-rank Actinobacteria were the dominant communities when the temperature increased to the highest point.…”
Section: Discussionmentioning
confidence: 99%
“…The colonies were picked and restreaked until the strain was axenic, and the pure culture was deposited in the China Center for Type Culture Collection (CCTCC) under the accession number AB206328. Strain CDF has the ability to degrade chicken feathers, and three proteases of this bacterium have been previously characterized, including a spore-associated protease (6), a subtilisin-like keratinolytic protease (7), and a glutamyl endopeptidase (8).…”
Section: Announcementmentioning
confidence: 99%
“…ET precursors contain only a secretory leader [3] and, therefore, are processed by signal peptidase. For bacterial GEPases similar to Glu-V8 and BIGEP, propeptide is removed heterocatalytically by different proteases [22, 100-104], with just one exception [21]. Comparison of the structures of the S1 sites of GEPases and the processing mechanisms shows that no explicit substrate charge compensator is revealed in the S1 pocket in autoactivated enzymes; the S1 site of ET is characterized by the presence of the Lys216 residue, while the GEPases similar to Glu–V8 and BIGEP processed heterocatalytically contain an α-amino group of the N-terminal residue.…”
Section: Structural Determinants Of Substrate Specificity and Maturatmentioning
confidence: 99%
“…Meanwhile, data have been published demonstrating that the precursors of Glu-V8 [113], BIGEP [109], Esp [7], as well as GEPases from B. licheniformis [114], B. subtilis [102], and Thermoactinomyces sp. [21] are capable of autoprocessing; in most cases, it is the bonds corresponding to the specificity of the mature enzymes that are cleaved [7, 21, 109, 114]. Furthermore, glutamate activity in trans of precursor analogues has been detected [100].…”
Section: Structural Determinants Of Substrate Specificity and Maturatmentioning
confidence: 99%
See 1 more Smart Citation